Object matters : Condoms, adolescence and time. - Vitellone, Nicole (UPSO - Manchester University Press E-Books., 2008)
During the mid 1980s the object of the condom became associated with the prevention of HIV/AIDS. In this book Nicole Vitellone investigates the consequences of this shift in the objects meaning. Focusing on the US, British and Australian contexts Object matters addresses the impact of the discourse of safer sex on our lives and in particular the lives of adolescents. Addressing AIDS public health campaigns, sex education policies, sex research on adolescence and debates on the eroticization of safer sex, the author looks at how the condom has affected our awareness of ourselves, of one another.